2015
DOI: 10.1007/s00423-015-1343-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and culture of primary human pancreatic stellate cells that reflect the context of their tissue of origin

Abstract: Primary human PSCs isolated from different contexts and cultured in a low-serum environment maintain a phenotype that reflects the stromal activity present in their tissue of origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…qRT-PCR was used to quantify SLURP1 and CHRNA7 mRNA expression in pancreatic tissues (8 specimen from organ donors, 13 CP specimen, and 45 PDAC specimen), in eight PDAC cell lines, and in the cultures of normal cells representing the major cell types in pancreatic lesions. The primary isolates have been done in our laboratory using pancreatic tissues (acinar and stromal pancreatic stellate cells/PSC preparations) and blood (immune preparations) as described previously [ 72 76 ]. Other cells have been purchased (endothelial HUVEC/HMDEC) or obtained as a kind gift (normal pancreatic immortalized cells HPDE6-E6E7-c7 cells; Dr. Ming-Sound Tsao).…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was used to quantify SLURP1 and CHRNA7 mRNA expression in pancreatic tissues (8 specimen from organ donors, 13 CP specimen, and 45 PDAC specimen), in eight PDAC cell lines, and in the cultures of normal cells representing the major cell types in pancreatic lesions. The primary isolates have been done in our laboratory using pancreatic tissues (acinar and stromal pancreatic stellate cells/PSC preparations) and blood (immune preparations) as described previously [ 72 76 ]. Other cells have been purchased (endothelial HUVEC/HMDEC) or obtained as a kind gift (normal pancreatic immortalized cells HPDE6-E6E7-c7 cells; Dr. Ming-Sound Tsao).…”
Section: Methodsmentioning
confidence: 99%
“…Quiescent PSCs could be activated in harmful conditions such as stress or inflammation, and the activation was demonstrated to be related to autophagy [ 18 ], an alternative metabolic pathway allowing tumor cells to obtain energy [ 19 ]. In addition, a recent study found that PSC activation levels could vary according to the microenvironment [ 20 ]. The typical features of activation are the expression of α-smooth muscle actin (α-SMA) and a significant quantity expression of ECM proteins (including collagen, laminin, fibronectin) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…В резуль-тате поражается эпителий протоков, который образует слепки и закупоривает протоки, тем самым вызывая воспалительные изменения и потерю функционирую-щей паренхимы ПЖ вследствие фиброза [4,6,7].…”
Section: îðèã³íàëüí³ äîñë³äAeåííÿunclassified